INVESTMENT ANALYSIS OF PTBA ASSET DEVELOPMENT IN PADANG, WEST SUMATRA - Berlyan Besoni; Sudarso Kaderi Wiryono (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the feasibility of investing in a four-star hotel development in Wisma Ombilin, Padang, as an effort to optimize idle assets owned by PT Bukit Asam Tbk (PTBA). Through qualitative and quantitative approaches, this study includes market, financial, risk, and economic and social benefit analyses. The results of the analysis indicate that this project is feasible with a Net Present Value (NPV) of IDR188.38 billion, an Internal Rate of Return (IRR) of 16.38% (exceeding the hurdle rate of 11.13%), and a Payback Period of 10.94 years. The hotel is projected to generate revenue from rooms (50%), F&B (20%), and MICE (30%), with the potential for significant contributions to the local economy through job creation. However, this project also faces risks such as fluctuations in room rates, occupancy rates, and loan interest rates. Mitigation strategies such as dynamic pricing, market diversification, and fixed-rate loans are recommended to minimize risks.